Sequential Innovation, Naked Exclusion, and Upfront Lump-Sum Payments - Jay Pil Choi; Christodoulos Stefanadis (Center for Economic Studies and ifo Institute (CESifo), 2017)
We present a potentially benign naked exclusion mechanism that can be applied to sequential innovation; a non-patentable original innovation by the incumbent supplier fosters derivative innovation by rivals. In the absence of an appropriate legal framework, the original innovator's equilibrium exclusivity contracts block subsequent efficient entry even if there is (leader-follower) competition in the contracting phase. However, the legal framework may maximize social welfare by imposing a ban on upfront lumps-sum payments in exclusivity contracts (by all suppliers) combined with an outright ban on exclusivity contracts by the derivative innovator. The former ban precludes the exclusion of socially beneficial derivative innovation by causing the incumbent supplier to resort to accommodation, rather than to pure exclusion, strategies. The latter ban complements the former by preventing inefficient or excessive derivative innovation.
Keywords: L42; D43; D45; 330; exclusivity; entry; fixed cost; lump-sum payment; sequential innovation